Cerebral Blood Flow Alterations in High Myopia: An Arterial Spin Labeling Study - Huihui Wang; Shanshan Li; Xi Chen; Yanling Wang; Jing Li; Zhenchang Wang (Neural Plasticity)
Objective. The aim of this study was to explore cerebral blood flow (CBF) alterations in subjects with high myopia (HM) using three-dimensional pseudocontinuous arterial spin labeling (3D-pcASL). Methods. A total of sixteen patients with bilateral HM and sixteen age- and sex-matched healthy controls (HCs) were recruited. All subjects were right-handed. Image data preprocessing was performed using SPM8 and the DPABI toolbox. Clinical parameters were acquired in the HM group. Two-sample t-tests and Pearson correlation analysis were applied in this study. Results. Compared to HCs, patients with HM exhibited significantly increased CBF in the bilateral cerebellum, and no decreases in CBF were detected in the brain. However, no relationship was found between the mean CBF values in the different brain areas and the disease duration (P>0.05). Conclusions. Using ASL analysis, we detected aberrant blood perfusion in the cerebellum in HM patients, contributing to a better understanding of brain abnormalities and brain plasticity through a different perspective.